2018
DOI: 10.1016/j.cmi.2018.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Identifying patients with bacterial infections using a combination of C-reactive protein, procalcitonin, TRAIL, and IP-10 in the emergency department: a prospective observational cohort study

Abstract: Objectives: The aim was to effectively reduce the unnecessary use of broad spectrum antibiotics in the emergency department (ED), patients with bacterial infections need to be identified accurately. We investigated the diagnostic value of a combination of biomarkers for bacterial infections, C-reactive protein (CRP), and procalcitonin (PCT), together with biomarkers for viral infections, tumour necrosis factor-related apoptosis-inducing ligand (TRAIL), and interferon-gamma-induced protein-10 (IP-10), in identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 15 publications
2
14
0
Order By: Relevance
“…P values were calculated by the independent samples t-test or the Mann-Whitney U test. sensitive to the risk of bacterial infections (Santolaya et al, 2008;Tang et al, 2011;Urbonas et al, 2012a;Urbonas et al, 2012b). Indeed, the levels of IL-6, IL-10, IFN-g, and TNF-a in our study, showed an upward trend.…”
Section: Discussionsupporting
confidence: 49%
“…P values were calculated by the independent samples t-test or the Mann-Whitney U test. sensitive to the risk of bacterial infections (Santolaya et al, 2008;Tang et al, 2011;Urbonas et al, 2012a;Urbonas et al, 2012b). Indeed, the levels of IL-6, IL-10, IFN-g, and TNF-a in our study, showed an upward trend.…”
Section: Discussionsupporting
confidence: 49%
“…The presence of TRAIL and IP-10 has been independently used to differentiate viral from bacterial infection. ( Oved et al, 2015 ; van der Does et al, 2016 , 2018 ; van Houten et al, 2017 ). Moreover, the hypothesis that TRAIL participates in sepsis by controlling inflammatory cell apoptosis and promotes inflammation resolution ( Renshaw et al, 2003 ).…”
Section: Discussionmentioning
confidence: 98%
“…Nevertheless, these results are still better than what has been historically observed with PCT, a finding reported by the test's manufacturer, and which highlights the potential improvements with a multimarker strategy. 67 van der Does et al 68 added to these findings regarding TRAIL/IP-10/CRP in a recently published study. In a cohort of 315 febrile patients in the ED, the 3-protein signature identified bacterial infections with an AUC of 0.73.…”
Section: Proteomic Approachesmentioning
confidence: 99%